THE FIRST EXPERIENCE OF USING THE «RANDEZVOUX» TECHNIQUE FOR HEPATICOJEJUNOANASTOMOSIS STRICTURE COMPLICATED INTRAHEPATIC CHOLANGIOLITHIASIS - A. V. Varabei; Y. N. Arlouski; N. A. Lagodich; V. F. Arehay (Вестник хирургии имени И.И. Грекова)
.